The emotional intelligence of senior executives and their effect on products innovation and on processes innovation - Blázquez Puerta, Carmen Dolores (2019)
Researchers have explored the antecedents and consequences of recovery satisfaction by creating, improving or using scales. However, scales should be invariant among contexts and cultures. Using item response theory, a methodological approach that helps measure items, we evaluated some constructs related to it. Results, limitations and future research are discussed.